Antimicrobial Effect of Extracellular Vesicles Derived From Human Oral Mucosal Epithelial Cells on Candida albicans - Zhao, Maomao; Zhang, Miaomiao; Xu, Kaiyuan; Wu, Kaihui; Xie, Ruiqi; Li, Ruowei; Wang, Qiong; Liu, Weida; Wang, Wenmei; Wang, Xiang (Frontiers in Immunology, 2022)
Candida albicans (C. albicans) is a commensal microorganism that colonizes the mucosal surfaces of healthy individuals. Changes in the host or environment can lead to overgrowth of C. albicans and infection of the host. Extracellular vesicles (EVs) are released by almost all cell types and play an increasingly recognized role in fighting microbial infection. The aim of the present study was to assess whether EVs derived from human oral mucosal epithelial (Leuk-1) cells can suppress the growth and invasion of C. albicans. The in vitro efficacy of Leuk-1-EVs against C. albicans was assessed by optical microscopy, laser scanning confocal microscopy, scanning electron microscopy, and transmission electron microscopy. The germ tube formation rate, the percentage of hyphae and the microcolony optical density were also used to analyze the growth of C. albicans in a coculture model with Leuk-1 cells and EVs or after inhibition of the secretion of EVs. A mouse model of oral candidiasis was established and submucosal injection of Leuk-1-EVs in the tongue was performed. Macroscopic observation, H&E staining, PAS staining, and scanning electron microscopy were used to assess antifungal effects of Leuk-1-EVs in vivo. The in vitro results showed that the growth of C. albicans was inhibited and that the morphology and ultrastructure were changed following Leuk-1-EVs treatment. The in vivo results exhibited that white lesions of the tongue, C. albicans infection, and oral mucosal inflammation of the infected mice were significantly alleviated after Leuk-1-EVs treatment. We thus reveal an antifungal capability of EVs derived from oral epithelial cells against C. albicans that is mediated by direct damage effects and potential synergy between EVs and human oral mucosal epithelial cells. This finding offers an intriguing, previously overlooked method of antifungal defense against C. albicans.